2016
DOI: 10.1111/ecc.12593
|View full text |Cite
|
Sign up to set email alerts
|

Development and feasibility of a web-based question prompt sheet to support information provision of health-related quality of life topics after oesophageal cancer surgery

Abstract: We developed a web-based question prompt sheet (QPS) to support information provision of health-related quality of life (HRQL) topics after oesophageal cancer surgery. The QPS was evaluated and updated in three consecutive studies. In Study 1, eight patients were guided in using the QPS. Feasibility was assessed by cognitive walkthrough, questionnaire and interview. We obtained 430 notes (217 negative, 213 positive) of patients' actions and or remarks, and 91 suggestions. With minor support, most patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Digital health interventions provide patients with evidence-based interventions through software apps. The availability of QPLs through these technologies is increasing [ 55 , 105 , 106 ]. Digital health interventions are easily accessible to patients from their homes through mobile devices or websites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital health interventions provide patients with evidence-based interventions through software apps. The availability of QPLs through these technologies is increasing [ 55 , 105 , 106 ]. Digital health interventions are easily accessible to patients from their homes through mobile devices or websites.…”
Section: Discussionmentioning
confidence: 99%
“…Most QPLs that are already available address early cancers [ 39 , 49 ] or palliative care [ 41 , 50 - 52 ], specific clinical situations (eg, early breast cancer [ 53 ], esophageal cancer [ 54 , 55 ], and myelodysplastic syndrome [ 56 ]), care circumstances (eg, clinical trials [ 57 , 58 ]), and populations (eg, older patients with cancer [ 58 ] or cultures or ethnicity [ 53 , 59 ])…”
Section: Introductionmentioning
confidence: 99%
“…Other QPLs are being developed to respond to the specific clinical issues relating to particular types of tumor [47,48]. In this context, Langbecker et al [49] have developed a QPL specifically adapted to patients with a brain tumor.…”
Section: Adaptation To the Care Trajectory And To The Type Of Cancermentioning
confidence: 99%
“…Finally, other authors have focused on particular types of oncology treatment. For instance, Jacobs et al [48] focused on the impact of surgery on quality-of-life for patients with esophageal cancer, and in their QPL they included elements relevant to the postsurgery period, such as physical activity, diet or specific care needs. QPLs have also been developed to accompany patients in their choice to take part in a clinical trial.…”
Section: Adaptation To the Care Trajectory And To The Type Of Cancermentioning
confidence: 99%
“…Research has shown that their use is associated with more question asking by patients, higher levels of information satisfaction, and a reduction of unmet information needs [14,[29][30][31][32][33]. Patients rate QPL as helpful [30,[34][35][36][37][38] and are more satisfied with consultations in which QPL were used [39].…”
Section: Introductionmentioning
confidence: 99%